Interventions for treating peripartum cardiomyopathy to improve outcomes for women and babies - Carlin, Andrew J (2010)
BACKGROUND: Peripartum cardiomyopathy (PPCM or PCMO) is a rare disease of unknown etiology, characterised by an acute onset of heart failure in women in the late stage of pregnancy or in the early months postpartum. OBJECTIVES: To assess the effectiveness and safety of any intervention for the care of women and/or their babies with a diagnosis of peripartum cardiomyopathy. SEARCH METHODS: We searched the Cochrane Pregnancy and Childbirth Group’s Trials Register (27 July 2010) and the reference lists of identified studies. SELECTION CRITERIA: Randomised and quasi-randomised controlled trials of any intervention for treating peripartum cardiomyopathy. Such interventions include: drugs; cardiac monitoring and treatment; haemodynamic monitoring and treatments; supportive therapies and heart transplant. DATA COLLECTION AND ANALYSIS: Two authors independently assessed the studies for inclusion, assessed risk of bias and carried out data extraction. Data entry was checked. MAIN RESULTS: We identified and included one pilot study, involving 20 women, undertaken in South Africa. Women were diagnosed postnatally and included in the study within 24 hours of diagnosis. AUTHORS’ CONCLUSIONS: There are insufficient data to draw any firm conclusions. Treatment with bromocriptine appears promising, although women would be unable to breastfeed due to suppression of lactation.